A devil and her love song. Volume 11 - Tōmori, Miyoshi; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2013)
"Maria finally gets to be with her beloved Shin, but her mysterious inability to speak continues to haunt her. Because the cause may be related to her past, she decides to go to Yokosuka, the town she grew up in. What life-changing surprises await her there?" -- p. [4] of cover.